Multifunctional binder as well as preparation method and application thereof
By copolymerizing monomers containing carbon-carbon double bonds and strong polar functional groups and monomers containing carbon-carbon double bonds and carboxylic acid groups, a multifunctional binder was developed, which solved the problems of insufficient bonding strength and poor adaptability of existing binders, and achieved efficient improvement in battery performance.
Patent Information
- Application Number
- CN202411940356.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-25
AI Technical Summary
The existing adhesives have insufficient bond strength, easy cracking, weak surface passivation ability, poor conductivity, expensive price, complicated preparation process, and single properties, making it difficult to adapt to different electrode materials.
A multifunctional binder is developed to form a copolymer of a rich hydrogen bond network and a strong polar group in the molecular chain by copolymerizing the first monomer containing a carbon-carbon double bond and a strong polar group and a second monomer containing a carbon-carbon double bond and a carboxylic acid group/carboxylate group.
It achieves high bond strength, good flexibility, wide adaptability, low cost and simple preparation, and can form strong hydrogen bonds and ion bonds with electrode active materials, improving the cycling and rate performance of the battery.
Smart Images

Figure CN119684502A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery material technology, and more specifically, relates to a multifunctional adhesive, a preparation method thereof, and an application thereof. Background Art
[0002] In recent years, with the in-depth research on battery active electrode materials and electrolytes, the shortcomings of batteries such as low first coulomb efficiency, poor rate performance, and insufficient cycle stability have been gradually improved. However, there are still few attempts to research and develop new binders. As an indispensable part of battery components, binders can tightly connect electrode active materials, conductive agents, and current collectors during charging and discharging. In addition, binders are also the connection points of electron transmission channels, which can improve the wettability of the electrode particle surface and the electrolyte interface and promote the transmission of ions.
[0003] Traditional polyvinylidene fluoride (PVDF), as a representative of oil-based binders, connects electrode components through van der Waals forces, which is conducive to material dispersion, but its bonding strength is insufficient and the cost is high; carboxymethyl cellulose (CMC) and polyacrylic acid (PAA) are representatives of water-based binders, which connect battery components through covalent bonds and hydrogen bonds, and have high bonding strength, but the pole pieces prepared by them are brittle and easy to crack. In order to improve the problems of traditional binders, patent document CN112159638A discloses an aqueous dendritic binder, which is made by grafting unsaturated olefin monomer polymers on nanocellulose main chains; patent document CN111384397A discloses an aqueous silicon-based lithium-ion battery negative electrode composite binder, which is made by adding two unsaturated olefin monomers to a ready-made polymer aqueous solution and then polymerizing them. The above technology improves the performance of the original polymer by introducing new polymers, and can be adapted to the silicon-carbon negative electrode system with a large volume expansion, but it still has the following defects: a polymer is still required as a substrate, and new materials are introduced to modify the original high molecular polymer (nanocellulose, chitosan, sodium alginate, etc.) to achieve performance improvement. The preparation process is complicated and is limited by the uneven mass distribution of the high molecular polymer in the raw materials. It is difficult to achieve precise control of the molecular weight of the final product, and it is only suitable for a single electrode material system that is insensitive to water.
[0004] Therefore, it is of great significance to develop a binder with simple synthesis process, high bonding strength, good flexibility, which can adapt the electrode active material to the water-based and oil-based binder systems by simply replacing the synthetic solution system, and can synergistically improve the electrochemical properties of the battery such as the first efficiency, cycle performance, and rate performance. Summary of the invention
[0005] In view of the defects of the prior art, the purpose of this application is to provide a multifunctional adhesive, a preparation method and application thereof, aiming to solve the problems of the existing adhesives such as insufficient bonding strength, easy cracking, weak surface passivation ability, poor conductivity, high price, complex preparation process, and single properties of the prepared adhesive.
[0006] To achieve the above-mentioned objectives, in a first aspect, the present application provides a multifunctional adhesive, which includes a copolymer, wherein the polymerization monomers of the copolymer are a first monomer and a second monomer; wherein the first monomer is a compound containing a carbon-carbon double bond and a strongly polar functional group; the second monomer is a compound containing a carbon-carbon double bond and a carboxylic acid group / carboxylate group, and the relative molecular weight of the second monomer is less than or equal to 200.
[0007] Preferably, the mass ratio of the first monomer to the second first monomer is (0.1-5):1.
[0008] Preferably, the highly polar functional group is selected from one or more of a sulfonate group, a phosphate group, a nitro group and a halogenated group.
[0009] Preferably, the first monomer is selected from one or more of sodium p-styrene sulfonate, sodium vinyl sulfonate, sodium allyl sulfonate, sodium propylene sulfonate, sodium methacrylate sulfonate, lithium propylene sulfonate, lithium methacrylate sulfonate, allyl diethyl phosphate, oleyl phosphate, 1-dimethylamino-2-nitrostyrene, (2-nitrovinyl)benzene, trans-β-nitrostyrene, 3-nitrostyrene, 4-nitrostyrene, 1,1-dimethylthionitrostyrene, 3-bromostyrene, 3-fluorostyrene, and 3-(trifluoromethyl)styrene.
[0010] Preferably, the relative molecular weight of the second monomer is 50-200, more preferably 70-150.
[0011] More preferably, the second monomer is selected from one or more of acrylic acid, methacrylic acid, maleic acid, 2,4-hexadienoic acid, sodium acrylate, lithium acrylate, sodium methacrylate, lithium methacrylate, sodium maleate, and lithium maleate.
[0012] In a second aspect, the present application provides a method for preparing the above-mentioned multifunctional adhesive, comprising the following steps: The second monomer and the first monomer are mixed in a solvent, an initiator is added or a light source is used to initiate the polymerization reaction, and then the mixture is heated and stirred in a gas atmosphere to perform a polymerization reaction, and then dried to prepare a multifunctional adhesive.
[0013] Preferably, the solvent is selected from one or more of water, ether solvents, ester solvents, ketone solvents, sulfone solvents, nitrogen-containing solvents, and aromatic hydrocarbon solvents.
[0014] Preferably, the initiator is selected from one or more of an organic peroxide initiator, an organic azo initiator, and an inorganic peroxide initiator.
[0015] Preferably, the light source is visible light or ultraviolet light.
[0016] Preferably, the gas atmosphere is selected from one or more of air, nitrogen, argon, helium and carbon dioxide.
[0017] Preferably, the heating temperature is 50°C to 150°C, more preferably 60°C to 120°C.
[0018] Preferably, the stirring speed is 150 rpm to 350 rpm.
[0019] Preferably, the polymerization reaction time is 1 h to 48 h, more preferably 4 h to 36 h.
[0020] In a third aspect, the present application provides a composite electrode material comprising the above-mentioned multifunctional binder.
[0021] Preferably, the composite electrode material further comprises an electrode active material; the multifunctional binder can form strong hydrogen bonds and ionic bonds with the electrode active material, thereby improving the cycle performance of the battery.
[0022] In a fourth aspect, the present application provides a battery electrode sheet, which includes a current collector and a composite electrode material layer disposed on at least one side surface of the current collector, wherein the material of the composite electrode material layer includes the above-mentioned composite electrode material.
[0023] In a fifth aspect, the present application provides an electrochemical energy storage device, which includes at least one of the above-mentioned multifunctional binder, the above-mentioned composite electrode material or the above-mentioned battery electrode sheet.
[0024] Preferably, the electrochemical energy storage device is any one of a lithium ion battery, a sodium ion battery, a supercapacitor, a fuel cell or a solar cell.
[0025] In general, the above technical solutions conceived by this application have the following technical advantages compared with the prior art: (1) The multifunctional binder provided in the present application includes a copolymer, wherein the polymerized monomers of the copolymer are a first monomer containing a carbon-carbon double bond and a strong polar functional group and a second monomer containing a carbon-carbon double bond and a carboxylic acid group / carboxylate group. The present application designs the molecular structure of the binder by selecting suitable polymerized monomers and regulating the ratio between the polymerized monomers, thereby preparing a binder containing a rich hydrogen bond network and strong polar groups in the molecular chain. The above-mentioned binder is used in a secondary battery, and the binder can form strong hydrogen bonds and ionic bonds with the electrode active material, so that the electrode active material is tightly combined with the current collector during the cycle process, thereby strengthening the bonding ability of the electrode sheet. At the same time, the binder can effectively passivate the defects on the surface of the electrode active material, improve the first coulombic efficiency of the battery, and enhance the cycle performance of the battery. In addition, the rich hydrogen bond network and strong polar groups in the molecular chain of the above-mentioned binder can optimize the ion transmission channel and improve the rate performance of the battery.
[0026] (2) Compared with existing binders, the multifunctional binder provided in this application has the advantages of simple synthesis route, simple preparation process, convenient operation, low preparation cost, and environmental friendliness. At the same time, it can synergistically improve the first coulombic efficiency, rate performance and cycle performance of the battery, has extremely high economic benefits, and is suitable for industrial production applications.
[0027] (3) The present application selects suitable polymerizable monomers and adjusts the ratio between the polymerizable monomers, thereby simply replacing the polymerizable monomers in the solution system for the polymerization reaction, thereby being able to prepare water-based binders and oil-based binders, which can be adapted to electrode active materials of different properties, and effectively solves the problem that the existing preparation method can only prepare binders of a single property. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The cyclic voltammetry curve of the secondary sodium ion battery prepared in Example 1 of the present application at a scan rate of 0.01 mV / S; Figure 2 The AC impedance spectra of the secondary sodium ion battery prepared in Example 1 of the present application before and after cycling; Figure 3 The rate performance of the secondary sodium ion battery prepared in Example 1 and Comparative Example 1 of the present application at 0.1C, 0.2C, 0.5C, and 1C; Figure 4 The cycle performance of the secondary sodium ion battery prepared in Example 1 and Comparative Examples 1-2 of the present application at 0.2C; Figure 5 Optical photographs of the negative electrode sheets observed after disassembling the secondary sodium ion batteries prepared in Example 1 and Comparative Examples 1-2 of the present application after cycling 700 times at 1C, wherein Figure 5 Content a is Example 1, Figure 5Content b is control example 1, Figure 5 Content c is control example 2; Figure 6 The cycle performance of the secondary lithium ion battery prepared in Example 16 of the present application and Comparative Examples 4-5 at 1C; Figure 7 The adhesion of the electrode active material on the surface of the copper foil current collector is tested after the electrode sheets prepared in Example 1, Example 16, Comparative Examples 1-2, and Comparative Examples 4-5 of the present application are subjected to a peeling test. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0030] In the specification and claims of the present application, the terms "first" and "second" etc. are used to distinguish different objects rather than to describe the specific order of the objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features.
[0031] In the description of this application, the term "and / or" is a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The symbol " / " in this article indicates that the associated objects are in an or relationship, for example, A / B means A or B.
[0032] In the description of this application, words such as "exemplary" or "for example" are used to indicate examples, illustrations or explanations. Any embodiment or design described as "exemplary" or "for example" in the embodiments of this application should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of words such as "exemplary" or "for example" is intended to present related concepts in a specific way.
[0033] In the description of this application, unless otherwise specified, "plurality" means two or more.
[0034] The present application provides a multifunctional adhesive, which includes a copolymer, wherein the polymerization monomers of the copolymer are a first monomer and a second monomer; wherein the first monomer is a compound containing a carbon-carbon double bond and a strong polar functional group; the second monomer is a compound containing a carbon-carbon double bond and a carboxylic acid group / carboxylate group, and the relative molecular weight of the second monomer is less than or equal to 200.
[0035] It is understandable that the second monomer is a compound containing a carbon-carbon double bond and a carboxylic acid group, or a compound containing a carbon-carbon double bond and a carboxylate group.
[0036] The multifunctional binder provided in the present application is a multi-polymer formed by polymerization of specific monomers, and the above-mentioned multifunctional binder polymer molecular chain contains carboxylic acid groups / carboxylate groups and strong polar groups. When the above-mentioned multifunctional binder is used to prepare battery pole pieces, the carboxylic acid groups / carboxylate groups and strong polar groups in the above-mentioned multifunctional binder molecular chain can form strong hydrogen bonds and ionic bonds with the electrode active material. Through the joint action of the carboxylic acid groups / carboxylate groups and strong polar groups on the polymer molecular chain, the electrode active material is closely combined with the current collector during the cycle process, and the bonding ability of the pole piece is strengthened. At the same time, the above-mentioned binder can effectively passivate the defects on the surface of the electrode active material, improve the first coulomb efficiency of the battery negative electrode, and enhance the cycle performance of the battery. In addition, the rich hydrogen bond network and strong polar groups in the above-mentioned binder molecular chain can optimize the ion transmission channel and improve the rate performance of the battery. The present application selects suitable polymerized monomers and regulates the ratio between polymerized monomers, so that the aqueous binder and the oil-based binder can be prepared by simply replacing the solution system of the polymerized monomer for polymerization reaction, which effectively solves the problem that the existing preparation method can only prepare a single-property binder.
[0037] In some embodiments, the mass ratio of the first monomer to the second monomer is (0.1-5):1.
[0038] In a preferred embodiment, the mass ratio of the first monomer to the second monomer is (0.2-5):1.
[0039] In some embodiments, the highly polar functional group is selected from one or more of a sulfonate group, a phosphate group, a nitro group and a halide group.
[0040] In some embodiments, the first monomer is selected from one or more of sodium p-styrene sulfonate, sodium vinyl sulfonate, sodium allyl sulfonate, sodium propylene sulfonate, sodium methacrylate sulfonate, lithium propylene sulfonate, lithium methacrylate sulfonate, allyl diethyl phosphate, oleyl phosphate, 1-dimethylamino-2-nitrostyrene, (2-nitrovinyl)benzene, trans-β-nitrostyrene, 3-nitrostyrene, 4-nitrostyrene, 1,1-dimethylthionitrostyrene, 3-bromostyrene, 3-fluorostyrene, and 3-(trifluoromethyl)styrene.
[0041] In some embodiments, the first monomer is selected from one or more of sodium vinyl sulfonate, sodium allyl sulfonate, sodium propylene sulfonate, sodium methyl propylene sulfonate, lithium propylene sulfonate, lithium methyl propylene sulfonate, and 1-dimethylamino-2-nitroethylene, so that a water-based binder and an oil-based binder can be prepared by simply replacing the solution system for the polymerization reaction of the polymerization monomer, which can be adapted to electrode active materials of different properties and effectively solves the problem that the existing preparation method can only prepare a binder of a single property.
[0042] In some embodiments, the relative molecular weight of the second monomer is 50-200, preferably 70-150.
[0043] In a preferred embodiment, the second monomer is selected from one or more of acrylic acid, methacrylic acid, maleic acid, 2,4-hexadienoic acid, sodium acrylate, lithium acrylate, sodium methacrylate, lithium methacrylate, sodium maleate, and lithium maleate.
[0044] On the other hand, the present application provides a method for preparing the above-mentioned multifunctional adhesive, comprising the following steps: The first monomer and the second monomer are mixed in a solvent, an initiator is added or a light source is used to initiate the polymerization reaction, and then the mixture is heated and stirred in a gas atmosphere to perform a polymerization reaction, and then dried to prepare a multifunctional adhesive.
[0045] In some embodiments, before the polymerization reaction is carried out, sodium hydroxide is added for sodium treatment, or lithium hydroxide is added for lithium treatment. It is understandable that those skilled in the art can choose to carry out sodium treatment or lithium treatment according to the application scenario of the binder. For example, when preparing a binder suitable for sodium ion batteries, sodium hydroxide can be added for sodium treatment. In some embodiments, the degree of sodium treatment / lithiation is 0% to 100%, preferably 50% to 80%, wherein the degree of sodium treatment / lithiation is the molar ratio of the Bronsted acid substituted by sodium or lithium after adding sodium hydroxide or lithium hydroxide to the total Bronsted acid in the polymerized monomer to which sodium hydroxide or lithium hydroxide is not added. In some embodiments, when the second monomer is one or more of sodium acrylate, lithium acrylate, sodium methacrylate, lithium methacrylate, sodium maleate, and lithium maleate, the degree of lithium treatment / lithiation is 100%.
[0046] It is understandable that those skilled in the art can select a suitable type of solvent according to the application scenario of the binder. The above-mentioned solvent can be an organic solvent or water, or a combination of the two. In some embodiments, the above-mentioned solvent includes but is not limited to water, nitrogen-containing solvents, alcohol solvents, ester solvents, ether solvents, ketone solvents, sulfone solvents, aromatic hydrocarbon solvents, etc.
[0047] In some embodiments, the nitrogen-containing solvents include but are not limited to N,N-dimethylformamide, N,N-dimethylacetamide, N,N-dimethylacetamide, N-methylpyrrolidone, etc.
[0048] In some embodiments, the alcohol solvents include but are not limited to methanol, ethanol, etc.
[0049] In some embodiments, the aromatic hydrocarbon solvents include but are not limited to benzene, toluene, xylene, etc.
[0050] In some embodiments, the ester solvents include but are not limited to ethylene carbonate, diethyl carbonate, methyl ethyl carbonate, propylene carbonate, etc.
[0051] In some embodiments, the ether solvent includes but is not limited to diethylene glycol dimethyl ether or tetrahydrofuran.
[0052] In some embodiments, the ketone solvents include but are not limited to acetone, methyl n-butyl ketone, methyl isobutyl ketone or cyclohexanone.
[0053] In some embodiments, the sulfone solvents include but are not limited to dimethyl sulfoxide or sulfolane.
[0054] In some embodiments, in order to allow the polymerization reaction to proceed more fully, the mass fraction of the above-mentioned polymerization monomer in the above-mentioned solvent is 30% to 70%.
[0055] In some embodiments, the initiator is selected from one or more of an organic peroxide initiator, an organic azo initiator, an inorganic peroxide initiator and an alkaline earth metal.
[0056] In some embodiments, the organic peroxide initiator includes but is not limited to benzoyl peroxide, diisopropylbenzene peroxide, tert-butyl benzoyl peroxide, methyl ethyl ketone peroxide, and the like.
[0057] In some embodiments, the above-mentioned organic azo initiator includes but is not limited to azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, etc.
[0058] In some embodiments, the inorganic peroxide initiator includes but is not limited to ammonium persulfate, sodium persulfate, potassium persulfate, etc.
[0059] In some embodiments, the amount of the initiator is 1% to 5% of the total mass of the polymerization monomers.
[0060] In some embodiments, the light source is visible light or ultraviolet light.
[0061] In some embodiments, the gas atmosphere is selected from one or more of air, nitrogen, argon, helium, and carbon dioxide.
[0062] In some embodiments, the heating temperature is 50°C to 150°C, preferably 60°C to 120°C.
[0063] In some embodiments, the stirring speed is 150 rpm to 350 rpm.
[0064] In some embodiments, the polymerization reaction time is 1 h to 48 h, preferably 4 h to 36 h.
[0065] It is understood that the present application does not specifically limit the above-mentioned drying conditions, and those skilled in the art can select appropriate drying temperature and time according to the solvent selected for the polymerization reaction, as long as a solid binder can be obtained, it is within the protection scope of the present application. In some embodiments, the above-mentioned drying temperature is 50°C to 200°C, and the time is 1h to 24h.
[0066] The present application also provides a composite electrode material, which includes the multifunctional binder.
[0067] In some embodiments, the composite electrode material further includes an electrode active material; the binder can form strong hydrogen bonds and ionic bonds with the electrode active material, and when the composite electrode material is used in a secondary battery, the cycle performance of the battery can be improved.
[0068] In a preferred embodiment, the composite electrode material further comprises one or more of a conductive material, a viscosity modifier, a filler, a cross-linking promoter, a coupling agent and an adhesion promoter.
[0069] It can be understood that the above-mentioned electrode active material includes a negative electrode active material or a positive electrode active material.
[0070] In some embodiments, the negative electrode active material includes carbon-based materials and / or silicon-based materials. The carbon-based materials include but are not limited to graphite, hard carbon, carbon black, carbon nanotubes, carbon fibers, mesophase carbon microspheres, petroleum coke, etc. The silicon-based materials include but are not limited to nano-silicon, micron silicon, porous silicon, amorphous silicon, silicon oxide, etc.
[0071] In a preferred embodiment, the composite electrode material comprises the multifunctional binder, the negative electrode active material and a conductive agent. Further preferably, in the composite electrode material, the mass percentage of the multifunctional binder is 5% to 15%. The conductive agent includes but is not limited to conductive carbon black, Ketjen black, acetylene black, conductive carbon balls, conductive graphite, carbon nanotubes, conductive carbon fibers, graphene and reduced graphene oxide.
[0072] In some embodiments, the positive electrode active material includes but is not limited to lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium copper oxide and lithium vanadium oxide.
[0073] The present application also provides a battery pole piece, which includes a current collector and a composite electrode material layer arranged on at least one side surface of the current collector, and the composite electrode material layer includes the multifunctional binder.
[0074] In some embodiments, the current collector includes but is not limited to copper foil, aluminum, carbon, etc.
[0075] The present application also provides a method for preparing the above-mentioned battery pole piece, comprising the following steps: forming an electrode mixture comprising the above-mentioned composite electrode material and a dispersant, then casting the above-mentioned electrode mixture on the surface of a current collector, and obtaining the battery pole piece after drying.
[0076] It is understandable that those skilled in the art can select a dispersant suitable for preparing a battery electrode. In some embodiments, the dispersant includes but is not limited to water, ethanol, propanol, butanol, N-methylpyrrolidone, and mixtures thereof.
[0077] In some embodiments, the battery electrode sheet can be used as a negative electrode sheet or a positive electrode sheet.
[0078] In some embodiments, the positive electrode sheet can be prepared by applying a composite electrode material containing the above-mentioned binder and positive electrode active material to a positive electrode current collector and drying. In some embodiments, the above-mentioned positive electrode active material includes but is not limited to lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium copper oxide and lithium vanadium oxide. Materials that can be used as positive electrode current collectors include but are not limited to aluminum, nickel, titanium, etc.
[0079] The present application also provides an electrochemical energy storage device, characterized in that it comprises at least one of the above-mentioned multifunctional binder, the above-mentioned composite electrode material or the above-mentioned battery electrode sheet.
[0080] In some embodiments, the electrochemical energy storage device is any one of a lithium-ion battery, a sodium-ion battery, a supercapacitor, a fuel cell or a solar cell, and is more preferably a lithium-ion battery or a sodium-ion battery.
[0081] It should be understood that materials of the same or similar type, model, quality, nature or function as the reagents and instruments used in the following examples can be used to implement the present application. The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples can be obtained from commercial sources unless otherwise specified.
[0082] The following are examples and comparative examples: Example 1 The method for preparing a binder suitable for sodium ion batteries provided in this embodiment comprises the following steps: Mix 3g of the first monomer sodium p-styrene sulfonate and 20mL of deionized water, stir thoroughly until completely dissolved, and obtain a first monomer aqueous solution. Then add 7g of the second monomer acrylic acid (relative molecular weight of 72), 0.1g of initiator ammonium persulfate and 9.722g of 30% sodium hydroxide solution by mass to the first monomer aqueous solution, and mix to obtain a binder mother solution with a sodium content of 75%. Pass argon gas into the binder mother solution until the air in the bottle is exhausted, then place it on a heating table, stir at 150rpm for 16h at 75°C, and then dry to obtain a water-based binder.
[0083] The preparation process of the negative electrode sheet of the sodium ion battery provided in this embodiment is as follows: 0.4 g of hard carbon, 0.05 g of Super P and 0.05 g of the above binder were dispersed in 1.8 mL of deionized water and uniformly mixed to form a slurry. The slurry was coated on a 0.7 mm thick copper foil and dried at 100° C. for 16 h to obtain a negative electrode sheet for a sodium ion battery.
[0084] The preparation process of the secondary sodium ion battery provided in this embodiment is as follows: The above-mentioned sodium ion battery negative electrode sheet was cut into a circular sheet with a diameter of 14 mm and assembled into a CR2032 button battery; wherein the counter electrode was a metal sodium sheet, the diaphragm was a glass fiber diaphragm, the electrolyte was a 1 mol / L NaPF6 solution, and the solvent of the electrolyte was a mixture of EC and DEC in a volume ratio of 1:1.
[0085] Electrochemical tests were performed on the prepared secondary sodium ion battery: 1) Cycle performance test: Place the assembled button cell in a battery testing device and perform charge and discharge operations in constant current mode. The test voltage range for sodium ion batteries is 0~3V; the test voltage range for lithium ion batteries is 0~2V.
[0086] 2) Cyclic voltammetry test: Place the assembled button cell in an electrochemical workstation and scan the cell at a scan rate of 0.01 mV / S in a voltage range of 0~3 V.
[0087] 3) AC impedance test: Place the assembled button cell in an electrochemical workstation and measure the initial voltage as the open circuit voltage of the cell. The frequency range is 10mHz~100kHz and the amplitude is 0.005V.
[0088] The cyclic voltammetry curve of the secondary sodium ion battery prepared in Example 1 at a scan rate of 0.01 mV / S is as follows: Figure 1 As shown in the figure, the sharp peak near 0.1V and the broad peak in the range of 0.2~1.5V correspond to two different sodium ion storage mechanisms, the former corresponding to the adsorption of sodium ions on the defects of hard carbon, and the latter corresponding to the embedding of sodium ions in the hard carbon sheets. Figure 1 It can be seen that no other peaks appear in the cyclic voltammetry curve of the secondary sodium ion battery prepared in Example 1, indicating that the electrochemical performance of the binder prepared in Example 1 is stable and can stably exist and play a bonding role within the working voltage range of the hard carbon negative electrode. Figure 1 It can be seen that the cyclic voltammetry curves of the secondary sodium ion battery at different cycle numbers have a high degree of overlap, indicating that the binder prepared in Example 1 can effectively improve the reversibility of the hard carbon negative electrode.
[0089] Figure 2 Shown are the AC impedance spectra of the secondary sodium ion battery prepared in Example 1 before and after cycling. It can be seen that after one cycle, a solid electrolyte interface (SEI) is formed on the surface of the hard carbon negative electrode, which is reflected in the new SEI capacitance and resistance in the fitting circuit.
[0090] Example 2 The method for preparing a binder suitable for sodium ion batteries provided in this embodiment comprises the following steps: Mix 7.5g of the first sodium p-styrene sulfonate and 20mL of deionized water, stir thoroughly until completely dissolved, and obtain a first monomer aqueous solution. Then add 2.5g of the second monomer methacrylic acid (relative molecular weight of 86), 0.1g of initiator ammonium persulfate, and 2.907g of a 30% sodium hydroxide solution to the first monomer aqueous solution to obtain a binder mother solution with a sodium content of 75%. Pass argon gas into the binder mother solution until the air in the bottle is exhausted, then place it on a heating table, stir at 200rpm for 14h at 85°C, and dry it to obtain a water-based binder.
[0091] The same method as in Example 1 was used to prepare the negative electrode sheet of the sodium ion battery and assemble the secondary sodium ion battery.
[0092] Example 3 The method for preparing a binder suitable for sodium ion batteries provided in this embodiment comprises the following steps: Mix 3g of the first monomer sodium vinyl sulfonate and 20mL of deionized water, stir thoroughly until completely dissolved, and obtain a first monomer aqueous solution. Then add 7g of the second monomer sodium acrylate (relative molecular weight of 94) and 0.1g of initiator ammonium persulfate to the first monomer aqueous solution without adding sodium hydroxide solution to obtain a binder mother solution with a sodium degree of 100%. Pass argon gas into the binder mother solution until the air in the bottle is exhausted, then place it on a heating table, stir at 200rpm for 14h at 85°C, and then dry it to obtain a water-based binder.
[0093] The same method as in Example 1 was used to prepare the negative electrode sheet of the sodium ion battery and assemble the secondary sodium ion battery.
[0094] Example 4 The method for preparing a binder suitable for sodium ion batteries provided in this embodiment comprises the following steps: Mix 5g of the first monomer sodium p-styrene sulfonate and 20mL of deionized water, stir thoroughly until completely dissolved, and obtain a first monomer aqueous solution. Then add 5g of the second monomer sodium methacrylate (relative molecular weight of 108) and 0.1g of initiator ammonium persulfate to the first monomer aqueous solution, without adding sodium hydroxide solution, and mix to obtain a binder mother liquor with a sodium degree of 100%. Pass argon gas into the above binder mother liquor until the air in the bottle is exhausted, then place it on a heating table, stir at 200rpm at 85°C for 14h, and then dry to obtain a water-based binder.
[0095] The same method as in Example 1 was used to prepare the negative electrode sheet of the sodium ion battery and assemble the secondary sodium ion battery.
[0096] Example 5 The method for preparing a binder suitable for sodium ion batteries provided in this embodiment comprises the following steps: Mix 5g of the first monomer sodium p-styrene sulfonate and 20mL of deionized water, stir thoroughly until completely dissolved, and obtain a first monomer aqueous solution. Then add 5g of the second monomer sodium maleate (relative molecular weight of 138) and 0.1g of initiator ammonium persulfate to the first monomer aqueous solution, and mix to obtain a binder mother solution with a sodium degree of 100%. Pass argon gas into the binder mother solution until the air in the bottle is exhausted, then place it on a heating table, stir at 150rpm for 16h at 75°C, and then dry to obtain a water-based binder.
[0097] The same method as in Example 1 was used to prepare the negative electrode sheet of the sodium ion battery and assemble the secondary sodium ion battery.
[0098] Example 6 The method for preparing a binder suitable for sodium ion batteries provided in this embodiment comprises the following steps: Mix 5g of the first monomer sodium p-styrene sulfonate and 20mL of deionized water, stir thoroughly until completely dissolved, and obtain a first monomer aqueous solution. Then add 5g of the second monomer maleic acid (relative molecular weight of 116), 0.1g of initiator ammonium persulfate and 8.621g of 30% sodium hydroxide solution to the first monomer aqueous solution, and mix to obtain a binder mother solution with a sodium content of 75%. Pass argon gas into the binder mother solution until the air in the bottle is exhausted, then place it on a heating table, stir at 200rpm for 14h at 85°C, and then dry to obtain a water-based binder.
[0099] The same method as in Example 1 was used to prepare the negative electrode sheet of the sodium ion battery and assemble the secondary sodium ion battery.
[0100] Example 7 The method for preparing a binder suitable for sodium ion batteries provided in this embodiment comprises the following steps: 3g of the first monomer sodium vinyl sulfonate and 20mL of deionized water were mixed and stirred until completely dissolved to obtain a first monomer aqueous solution. Then, 7g of the second monomer acrylic acid and 0.1g of the initiator ammonium persulfate were added to the first monomer aqueous solution without adding sodium hydroxide solution to obtain a binder mother solution with a sodium content of 0%. Argon was introduced into the binder mother solution until the air in the bottle was exhausted, and then it was placed on a heating table, stirred at 200rpm for 14h at 85°C, and then dried to obtain a water-based binder.
[0101] The same method as in Example 1 was used to prepare the negative electrode sheet of the sodium ion battery and assemble the secondary sodium ion battery.
[0102] Example 8 The method for preparing a binder suitable for sodium ion batteries provided in this embodiment comprises the following steps: 3g of the first monomer sodium vinyl sulfonate, 2g of the first monomer sodium p-styrene sulfonate and 20mL of deionized water were mixed and stirred until completely dissolved to obtain a first monomer aqueous solution. Then, 5g of the second monomer acrylic acid, 0.1g of the initiator ammonium persulfate and 6.944g of a 30% by mass sodium hydroxide solution were added to the first monomer aqueous solution to obtain a binder mother solution with a sodium content of 75%. Argon was introduced into the binder mother solution until the air in the bottle was exhausted, and then it was placed on a heating table, stirred at 200 rpm for 14 hours at 85°C, and then dried to obtain a water-based binder.
[0103] The same method as in Example 1 was used to prepare the negative electrode sheet of the sodium ion battery and assemble the secondary sodium ion battery.
[0104] Example 9 The method for preparing a binder suitable for sodium ion batteries provided in this embodiment comprises the following steps: 3g of the first monomer sodium p-styrene sulfonate and 8mL of N,N-dimethylformamide were mixed and stirred until completely dissolved to obtain a first monomer organic solution. Then, 7g of the second monomer acrylic acid and 0.1g of the initiator azobisisobutyronitrile were added to the first monomer organic solution and mixed to obtain a binder mother solution. Argon gas was introduced into the binder mother solution until the air in the bottle was exhausted, and then it was placed on a heating table, stirred at 350 rpm for 8 hours at 70°C, and then dried to obtain an oil-based binder.
[0105] The same method as in Example 1 was used to prepare the negative electrode sheet of the sodium ion battery and assemble the secondary sodium ion battery.
[0106] Example 10 The method for preparing a binder suitable for sodium ion batteries provided in this embodiment comprises the following steps: 2g of the first monomer sodium p-styrene sulfonate, 1g of the first monomer 3-bromostyrene and 10mL of N,N-dimethylformamide were mixed and stirred until completely dissolved to obtain a first monomer organic solution. Then 7g of the second monomer acrylic acid and 0.1g of the initiator azobisisobutyronitrile were added to the first monomer organic solution, and mixed to obtain a binder mother solution with a sodium degree of 0%. Argon was introduced into the binder mother solution until the air in the bottle was exhausted, and then it was placed on a heating table, stirred at 350rpm for 8h at 70°C, and then dried to obtain an oil-based binder.
[0107] The same method as in Example 1 was used to prepare the negative electrode sheet of the sodium ion battery and assemble the secondary sodium ion battery.
[0108] Embodiment 11 The method for preparing a binder suitable for sodium ion batteries provided in this embodiment comprises the following steps: 3g of the first monomer sodium p-styrene sulfonate, 1g of the first monomer 3-bromostyrene, 0.5g of the first monomer 3-fluorostyrene and 8mL of N,N-dimethylformamide were mixed and stirred until completely dissolved to obtain a first monomer organic solution. Then 7g of the second monomer acrylic acid and 0.1g of the initiator azobisisobutyronitrile were added to the first monomer organic solution, and mixed to obtain a binder mother solution with a sodium degree of 0%. Argon was introduced into the binder mother solution until the air in the bottle was exhausted, and then it was placed on a heating table, stirred at 200 rpm at 60°C for 4h, and then stirred at 200 rpm at 80°C for 10h and dried to obtain an oil-based binder.
[0109] The same method as in Example 1 was used to prepare the negative electrode sheet of the sodium ion battery and assemble the secondary sodium ion battery.
[0110] Example 12 The method for preparing a binder suitable for sodium ion batteries provided in this embodiment comprises the following steps: Mix 3g of the first monomer 1-dimethylamino-2-nitroethylene and 20mL of N,N-dimethylformamide, stir thoroughly until completely dissolved, and obtain a first monomer organic solution. Then add 7g of the second monomer acrylic acid and 0.1g of the initiator azobisisobutyronitrile to the first monomer organic solution, and mix to obtain a binder mother solution with a sodium degree of 0%. Pass argon gas into the binder mother solution until the air in the bottle is exhausted, then place it on a heating table, stir at 200rpm at 65℃ for 2h, and then stir at 200rpm at 85℃ for 10h and dry to obtain an oil-based binder.
[0111] The same method as in Example 1 was used to prepare the negative electrode sheet of the sodium ion battery and assemble the secondary sodium ion battery.
[0112] Embodiment 13 The method for preparing a binder suitable for sodium ion batteries provided in this embodiment comprises the following steps: Mix 2g of the first monomer 3-(trifluoromethyl)styrene and 10mL of benzene, stir thoroughly until completely dissolved, and obtain a first monomer organic solution. Then add 6g of the second monomer acrylic acid and 0.1g of the initiator azobisisobutyronitrile to the above first monomer organic solution, and mix to obtain a binder mother solution with a sodium degree of 0%. Pass argon gas into the above binder mother solution until the air in the bottle is exhausted, then place it on a heating table, stir at 200rpm at 55°C for 4h, and then stir at 200rpm at 90°C for 10h and dry to obtain an oil-based binder.
[0113] The same method as in Example 1 was used to prepare the negative electrode sheet of the sodium ion battery and assemble the secondary sodium ion battery.
[0114] Embodiment 14 The method for preparing a binder suitable for sodium ion batteries provided in this embodiment comprises the following steps: 2g of the first monomer allyl diethyl phosphate and 10mL of tetrahydrofuran were mixed and stirred until completely dissolved to obtain a first monomer organic solution. Then 8g of the second monomer acrylic acid and 0.1g of the initiator dibenzoyl peroxide were added to the first monomer organic solution, and mixed to obtain a binder mother solution with a sodium degree of 0%. Argon was introduced into the binder mother solution until the air in the bottle was exhausted, and then it was placed on a heating table, stirred at 200rpm for 2h at 75°C, and then stirred at 200rpm for 12h at 90°C and dried to obtain an oil-based binder.
[0115] The same method as in Example 1 was used to prepare the negative electrode sheet of the sodium ion battery and assemble the secondary sodium ion battery.
[0116] Embodiment 15 The method for preparing a binder suitable for sodium ion batteries provided in this embodiment comprises the following steps: 3g of the first monomer 3-nitrostyrene and 10mL of benzene were mixed and stirred until completely dissolved to obtain a first monomer organic solution. Then, 7g of the second monomer acrylic acid and 0.1g of the initiator azobisisobutyronitrile were added to the first monomer organic solution, and mixed to obtain a binder mother solution with a sodium degree of 0%. Argon gas was introduced into the binder mother solution until the air in the bottle was exhausted, and then it was placed on a heating table in a dark environment, and under the irradiation of an ultraviolet lamp with a wavelength of 365nm, it was stirred at 200rpm at 75℃ for 2h, and then stirred at 200rpm at 96℃ for 12h and dried to obtain an oil-based binder.
[0117] The same method as in Example 1 was used to prepare the negative electrode sheet of the sodium ion battery and assemble the secondary sodium ion battery.
[0118] Comparative Example 1 The preparation process of the negative electrode sheet of the sodium ion battery provided in this comparative example is as follows: 0.4 g of hard carbon, 0.05 g of Super P and 0.05 g of binder carboxymethyl cellulose (aqueous binder) were dispersed in 1.8 mL of deionized water and mixed evenly to form a slurry. The slurry was coated on a 0.7 mm thick copper foil and dried at 100 ° C for 16 h to obtain a negative electrode sheet for a sodium ion battery.
[0119] The secondary sodium ion battery was assembled in the same manner as in Example 1, and electrochemical tests were performed.
[0120] Figure 3 Shown are rate performance graphs of the secondary sodium ion batteries prepared in Example 1 and Control Example 1 at 0.1C, 0.2C, 0.5C, and 1C. It can be seen that the secondary sodium ion battery prepared in Example 1 has a higher specific capacity than that in Control Example 1 at a high current rate of 1C, and the specific capacity can reach 227.3 mAh / g, indicating that the binder prepared in Example 1 can effectively improve the rate performance of the secondary sodium ion battery.
[0121] Comparative Example 2 The preparation process of the negative electrode sheet of the sodium ion battery provided in this comparative example is as follows: 0.4 g of hard carbon, 0.05 g of Super P and 0.05 g of binder polyvinylidene fluoride (oil-based binder) were dispersed in 1.8 mL of N-methylpyrrolidone and mixed evenly to form a slurry. The slurry was coated on a 0.7 mm thick copper foil and dried at 100 ° C for 16 h to obtain a negative electrode sheet for a sodium ion battery.
[0122] The secondary sodium ion battery was assembled in the same manner as in Example 1, and electrochemical tests were performed.
[0123] Figure 4The figure shows the cycle performance of the secondary sodium ion battery prepared in Example 1 and Comparative Examples 1-2 at 0.2C. It can be seen that compared with Comparative Examples 1-2, the secondary sodium battery prepared in Example 1 can still reach a specific capacity of 272.1mAh / g after 100 cycles, and the first coulombic efficiency is as high as 87.32%. The specific capacity retention rate after 100 cycles is above 95.0%, which has better cycle performance. The reason for this analysis may be that when the hard carbon material matching the binder provided in Example 1 of the present application is used to prepare the negative electrode sheet, the surface passivation ability is strong, and the surface defects of the hard carbon material can be effectively passivated, and the first coulombic efficiency of the hard carbon negative electrode is improved, which is beneficial to improving the cycle performance of the full sodium ion battery.
[0124] Figure 5 The optical photographs of the electrodes used after the secondary sodium ion batteries prepared in Example 1 and Comparative Examples 1-2 were disassembled after cycling 700 times at 1C are shown. It can be seen that the electrode structure of the sodium ion in Example 1 still maintains close contact with the copper foil current collector under high current and long cycle, and the electrode structure is intact, not cracked, smooth and without powder falling ( Figure 5 Content a); However, in the electrode structure of sodium ions in Comparative Examples 1 and 2, the active material and the current collector separated after a long cycle, and the electrode structure was destroyed ( Figure 5 Content b. Figure 5 Content c), which indicates that the binder prepared in the present application has excellent bonding properties and can ensure that the electrode structure remains stable during long cycles.
[0125] Comparative Example 3 The method for preparing a binder suitable for sodium ion batteries provided in this embodiment comprises the following steps: 3g of the first monomer sodium p-styrene sulfonate and 10mL of N-methylpyrrolidone were mixed and stirred until completely dissolved to obtain a first monomer organic solution. Then, 7g of the second monomer 2-tridecenoic acid (relative molecular weight of 212) and 0.1g of initiator azobisisobutyronitrile were added to the first monomer organic solution to obtain a binder mother solution with a sodium degree of 0%. Argon was introduced into the binder mother solution until the air in the bottle was exhausted, and then it was placed at 75°C and stirred at 200rpm for 2h, and then stirred at 96°C and 200rpm for 12h and dried to obtain an oil-based binder.
[0126] The same method as in Example 1 was used to prepare the negative electrode sheet of the sodium ion battery and assemble the secondary sodium ion battery.
[0127] Example 16 The method for preparing a binder suitable for lithium-ion batteries provided in this embodiment comprises the following steps: Mix 3g of the first monomer sodium p-styrene sulfonate and 20mL of deionized water, stir thoroughly until completely dissolved, and obtain a first monomer aqueous solution. Then add 7g of the second monomer acrylic acid, 0.1g of the initiator ammonium persulfate and 18.667g of a 10% lithium hydroxide solution by mass to the first monomer aqueous solution, and mix to obtain a binder mother solution with a lithiation degree of 80%. Pass argon gas into the binder mother solution until the air in the bottle is exhausted, then place it on a heating table, stir at 200rpm at 85°C for 14h, and then dry to obtain a water-based binder.
[0128] The preparation process of the negative electrode sheet of the lithium ion battery provided in this embodiment is as follows: 0.4 g of graphite, 0.05 g of Super P and 0.05 g of the above binder were dispersed in 2 mL of deionized water and uniformly mixed to form a slurry. The slurry was coated on a 0.7 mm thick copper foil and dried at 100° C. for 16 h to obtain a negative electrode sheet for a lithium ion battery.
[0129] The preparation process of the secondary lithium-ion battery provided in this embodiment is as follows: The above-mentioned lithium-ion battery negative electrode sheet was cut into a circular sheet with a diameter of 14 mm, and assembled into a CR2032 button battery; wherein the counter electrode was a metal lithium sheet, the diaphragm was a PP diaphragm, the electrolyte was a 1 mol / L LiPF6 solution, and the solvent of the electrolyte was a mixture of EC and DEC in a volume ratio of 1:1.
[0130] Embodiment 17 The method for preparing a binder suitable for lithium-ion batteries provided in this embodiment comprises the following steps: Mix 5g of the first monomer sodium p-styrene sulfonate and 20mL of deionized water, stir thoroughly until completely dissolved, and obtain a first monomer aqueous solution. Then add 5g of the second monomer acrylic acid, 0.1g of initiator ammonium persulfate and 13.333g of 10% by mass lithium hydroxide solution to the first monomer aqueous solution, and mix to obtain a binder mother solution with a lithiation degree of 80%. Pass nitrogen into the binder mother solution until the air in the bottle is exhausted, then place it on a heating table, stir at 200rpm at 85°C for 14h, and then dry to obtain a water-based binder.
[0131] The same method as in Example 16 was used to prepare the negative electrode sheet of the lithium ion battery and assemble the secondary lithium ion battery.
[0132] Embodiment 18 The method for preparing a binder suitable for lithium-ion batteries provided in this embodiment comprises the following steps: Mix 8.3g of the first monomer sodium p-styrene sulfonate and 20mL of deionized water, stir thoroughly until completely dissolved, and obtain a first monomer aqueous solution. Then add 1.7g of the second monomer acrylic acid, 0.1g of initiator ammonium persulfate and 4.533g of 10% by mass lithium hydroxide solution to the first monomer aqueous solution, and mix to obtain a binder mother solution with a lithiation degree of 80%. Pass nitrogen into the binder mother solution until the air in the bottle is exhausted, then place it on a heating table, stir at 200rpm at 85°C for 14h, and then dry to obtain a water-based binder.
[0133] The same method as in Example 16 was used to prepare the negative electrode sheet of the lithium ion battery and assemble the secondary lithium ion battery.
[0134] Embodiment 19 The method for preparing a binder suitable for lithium-ion batteries provided in this embodiment comprises the following steps: 3g of the first monomer sodium p-styrene sulfonate and 8 mL of N,N-dimethylformamide were mixed and stirred until completely dissolved to obtain a first monomer organic solution. Then, 7g of the second monomer acrylic acid and 0.1g of the initiator azobisisobutyronitrile were added to the first monomer organic solution without adding lithium hydroxide solution, and mixed to obtain a binder mother solution with a lithiation degree of 0%. Then, the binder mother solution was placed on a heating table, stirred at 350 rpm for 8 hours at 70°C, and then dried to obtain an oil-based binder.
[0135] The same method as in Example 16 was used to prepare the negative electrode sheet of the lithium ion battery and assemble the secondary lithium ion battery.
[0136] Embodiment 20 The preparation method of the binder suitable for lithium-ion batteries provided in this embodiment is the same as that in Example 16, and a water-based binder is prepared.
[0137] The preparation process of the positive electrode sheet of the lithium ion battery provided in this embodiment is as follows: 0.4 g of lithium iron phosphate, 0.05 g of Super P and 0.05 g of the above aqueous binder were dispersed in 2 mL of deionized water and uniformly mixed to form a slurry. The slurry was coated on a 0.7 mm thick copper foil and dried at 100° C. for 16 h to obtain a lithium ion battery positive electrode sheet.
[0138] The preparation process of the secondary lithium-ion battery provided in this embodiment is as follows: The above-mentioned lithium-ion battery positive electrode sheet was cut into a circular sheet with a diameter of 14 mm, and assembled into a CR2032 button battery; wherein the counter electrode was a metal lithium sheet, the diaphragm was a PP diaphragm, the electrolyte was a 1 mol / L LiPF6 solution, and the solvent of the electrolyte was a mixture of EC and DEC in a volume ratio of 1:1.
[0139] The electrochemical properties of the secondary lithium-ion battery assembled above were tested, and the results showed that after the battery was cycled 550 times at 1C, the capacity retention rate could reach 88.32%, which shows that the binder provided in this embodiment is also suitable for preparing positive electrode sheets and has excellent electrochemical properties.
[0140] Comparative Example 4 The preparation process of the negative electrode sheet of the lithium-ion battery provided in this comparative example is as follows: 0.4 g of graphite, 0.05 g of Super P and 0.05 g of binder carboxymethyl cellulose (aqueous binder) were dispersed in 2 mL of deionized water and mixed evenly to form a slurry. The slurry was coated on a 0.7 mm thick copper foil and dried at 100° C. for 16 h to obtain a negative electrode sheet for a lithium-ion battery.
[0141] The secondary lithium-ion battery was assembled in the same manner as in Example 16, and electrochemical tests were performed.
[0142] Comparative Example 5 The preparation process of the negative electrode sheet of the lithium-ion battery provided in this comparative example is as follows: 0.4 g of graphite, 0.05 g of Super P and 0.05 g of binder polyvinylidene fluoride (oil-based binder) were dispersed in 2 mL of N-methylpyrrolidone and mixed evenly to form a slurry. The slurry was coated on a 0.7 mm thick copper foil and dried at 100° C. for 16 h to obtain a negative electrode sheet for a lithium-ion battery.
[0143] The secondary lithium-ion battery was assembled in the same manner as in Example 16, and electrochemical tests were performed.
[0144] Figure 6 The cycle performance diagram of the secondary lithium-ion battery prepared in Example 17 and Comparative Examples 4-5 at 1C is shown. It can be seen that compared with Comparative Examples 4-5, the secondary lithium battery prepared in Example 16 can still reach a specific capacity of 313.7 mAh / g after 550 cycles, and the first coulomb efficiency is as high as 88.13%. The specific capacity retention rate after 550 cycles is above 94.7%, which has better cycle performance. The reason for the analysis may be that when the matching graphite material of the binder provided in Example 8 of the present application is used to prepare the negative electrode sheet, the surface passivation ability is strong, and the surface defects of the graphite material can be effectively passivated, and the first coulomb efficiency of the graphite negative electrode is improved, which is conducive to improving the cycle performance of the lithium-ion battery.
[0145] Comparative Example 6 The preparation method of the binder provided in this comparative example comprises the following steps: Mix 3g of the first monomer dimethyl (dimethylamino) vinyl silane (strong polar functional group is amino) and 10mL of tetrahydrofuran, stir thoroughly until completely dissolved, and obtain the first monomer organic solution. Then add 7g of the second monomer acrylic acid and 0.1g of the initiator azobisisobutyronitrile to the above first monomer organic solution, and mix to obtain a binder mother solution with a lithiation degree of 0%. Pass argon gas into the above binder mother solution until the air in the bottle is exhausted, then place it on a heating table, stir at 150rpm for 16h at 85°C, and then dry to obtain a binder.
[0146] The same method as in Example 16 was used to prepare the negative electrode sheet of the lithium ion battery and assemble the secondary lithium ion battery.
[0147] Comparative Example 7 The preparation method of the binder provided in this comparative example comprises the following steps: Mix 8.5g of the first monomer sodium p-styrene sulfonate and 20mL of deionized water, stir thoroughly until completely dissolved, and obtain a first monomer aqueous solution. Then add 1.5g of the second monomer acrylic acid, 0.1g of initiator ammonium persulfate and 2.500g of 10% by mass lithium hydroxide solution to the first monomer aqueous solution, and mix to obtain a binder mother solution with a lithiation degree of 50%. Pass nitrogen into the binder mother solution until the air in the bottle is exhausted, then place it on a heating table, stir at 200rpm at 85°C for 14h, and then dry to obtain a water-based binder.
[0148] The same method as in Example 16 was used to prepare the negative electrode sheet of the lithium ion battery and assemble the secondary lithium ion battery.
[0149] Comparative Example 8 The preparation method of the binder provided in this comparative example comprises the following steps: Mix 0.1g of the first monomer sodium p-styrene sulfonate and 20mL of deionized water, stir thoroughly until completely dissolved, and obtain a first monomer aqueous solution. Then add 9.9g of the second monomer acrylic acid, 0.1g of the initiator ammonium persulfate and 16.500g of a 10% by mass lithium hydroxide solution to the first monomer aqueous solution, and mix to obtain a binder mother solution with a lithiation degree of 50%. Pass nitrogen into the binder mother solution until the air in the bottle is exhausted, then place it on a heating table, stir at 200rpm at 75°C for 14h, and then dry to obtain a water-based binder.
[0150] The same method as in Example 16 was used to prepare the negative electrode sheet of the lithium ion battery and assemble the secondary lithium ion battery.
[0151] The cycle performance of the secondary sodium ion batteries assembled in Examples 1 to 15 and Comparative Examples 1 to 3 was tested for 100 cycles at 0.2C; the cycle performance of the secondary lithium ion batteries assembled in Examples 16 to 20 and Comparative Examples 4 to 8 was tested for 550 cycles at 1C. The results are shown in Table 1.
[0152] The electrode sheets prepared in the examples and control examples were peeled off according to the test method provided in GB / T2790-1995, the peeling strength was tested, and the adhesion of the electrode active material on the surface of the copper foil current collector was observed.
[0153] Table 1 Cycling performance of secondary batteries assembled from Examples 1 to 20 and Comparative Examples 1 to 8
[0154] It can be seen from Table 1 that the first coulombic efficiency of the secondary sodium-ion battery assembled using the binder prepared in this application is greater than 81%, and the specific capacity retention rate is higher than 80% after 100 cycles at 0.2C, which has excellent cycle performance. The first coulombic efficiency of the secondary lithium-ion battery assembled using the binder prepared in this application is greater than 85%, and the specific capacity retention rate is higher than 80% after 550 cycles at 1C, which has excellent cycle performance. It was further found that after the binder was treated with sodium / lithium, the first coulombic efficiency and cycle capacity retention rate of the battery were improved. The reason for this may be that the sodium / lithium ions contained in the binder after sodium / lithium treatment can participate in the battery cycle, increase the transmission speed of sodium / lithium ions in the battery, and thus improve the electrochemical performance. In addition, after the solvent used in the synthesis of the binder was switched from water to oil, the electrochemical performance of the battery assembled based on the binder decreased slightly, but was still at a high level and was still significantly better than the ordinary oil-based binder polyvinylidene fluoride. This shows that the binder prepared in the present application can achieve the adaptation of the electrode active material to the water-based / oil-based binder system by simply replacing the solvent, and a multifunctional binder can be prepared.
[0155] The cycle retention rate and peel strength of the secondary sodium ion battery assembled with the binder prepared in Comparative Example 3 are poor. This may be because the relative molecular weight of the second monomer is too large. Under a certain degree of polymerization, the molecular chain of the prepared binder is short and cannot maintain the tight connection of the electrode active material, resulting in the deterioration of the performance of the assembled battery.
[0156] The cycle capacity retention rate of the secondary lithium-ion battery assembled with the binder prepared in Control Example 6 is less than 80%. The possible reason is that the structure of the first monomer (dimethyl(dimethylamino)vinylsilane) is unstable and its compatibility with the electrode activity is poor, resulting in a significant decrease in the cycle performance of the battery, which does not meet the requirements.
[0157] The cycle capacity retention rate of the secondary lithium-ion battery assembled with the binder prepared in Control Example 7 is lower than 80%. The reason for this may be that the content of the second monomer is too low, resulting in a decrease in the molecular weight of the formed binder, changes in the spatial network structure of the binder, and a decrease in the mechanical properties of the battery pole piece, resulting in degradation of its long cycle performance. The first coulomb efficiency of the secondary lithium-ion battery assembled with the binder prepared in Control Example 8 is lower than 80%. The reason for this may be that the content of the first monomer is too low, resulting in a decrease in the overall polarity of the formed binder, a decrease in the electrochemical regulation ability, and a significant decrease in the first coulomb efficiency of the battery and degradation of the long cycle performance.
[0158] like Figure 7 As shown, after the pole pieces prepared in comparative examples 1-2 and 4-5 were stripped, the surface of the copper foil current collector was relatively smooth, and most of the electrode active materials adhered to the strong adhesive tape. After the pole pieces prepared in Examples 1 and 16 were stripped, the electrode active materials adhered to the copper foil current collector, which shows that the bonding force of the binder prepared in Examples 1 and 16 is better than the commonly used water-based binder carboxymethyl cellulose and oil-based binder polyvinylidene fluoride (i.e., comparative examples 1-2 and 4-5), and even higher than the strong adhesive tape, and has excellent bonding performance.
[0159] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A multifunctional adhesive, characterized in that: The multifunctional binder comprises a copolymer, wherein the polymerization monomers of the copolymer are a first monomer and a second monomer; the first monomer is a compound containing a carbon-carbon double bond and a strong polar functional group; The second monomer is a compound containing a carbon-carbon double bond and a carboxylic acid group / carboxylate group, and the relative molecular weight of the second monomer is less than or equal to 200.
2. The multifunctional adhesive according to claim 1, characterized in that: The mass ratio of the first monomer to the second monomer is (0.1-5):
1.
3. The multifunctional adhesive according to claim 1 or 2, characterized in that: The highly polar functional group is selected from one or more of a sulfonate group, a phosphate group, a nitro group and a halide group; Preferably, the first monomer is selected from one or more of sodium p-styrene sulfonate, sodium vinyl sulfonate, sodium allyl sulfonate, sodium propylene sulfonate, sodium methacrylate sulfonate, lithium propylene sulfonate, lithium methacrylate sulfonate, allyl diethyl phosphate, oleyl phosphate, 1-dimethylamino-2-nitrobenzene, (2-nitrovinyl)benzene, trans-β-nitrostyrene, 3-nitrostyrene, 4-nitrostyrene, 1,1-dimethylthionitrostyrene, 3-bromostyrene, 3-fluorostyrene, and 3-(trifluoromethyl)styrene.
4. The multifunctional adhesive according to claim 1 or 2, characterized in that: The relative molecular weight of the second monomer is 50-200; Preferably, the second monomer has a relative molecular weight of 70 to 150 and is selected from one or more of acrylic acid, methacrylic acid, maleic acid, 2,4-hexadienoic acid, sodium acrylate, lithium acrylate, sodium methacrylate, lithium methacrylate, sodium maleate, and lithium maleate.
5. A method for preparing the multifunctional adhesive according to any one of claims 1 to 4, characterized in that: The steps include: The first and second monomers are mixed in a solvent, an initiator is added or a light source is used for initiation, the mixture is heated and stirred in a gas atmosphere for polymerization reaction, and then dried to prepare a multifunctional adhesive.
6. The preparation method according to claim 5, characterized in that: The solvent is selected from one or more of water, ether solvents, ester solvents, ketone solvents, sulfone solvents, nitrogen-containing solvents, and aromatic hydrocarbon solvents; and / or, The initiator is selected from one or more of an organic peroxide initiator, an organic azo initiator, and an inorganic peroxide initiator; and / or, The light source is visible light or ultraviolet light; and / or, The gas atmosphere is selected from one or more of air, nitrogen, argon, helium, and carbon dioxide; and / or, The heating temperature is 50° C. to 150° C., the stirring speed is 150 rpm to 350 rpm, and the polymerization reaction time is 1 h to 48 h.
7. A composite electrode material, characterized in that: It comprises the multifunctional adhesive according to any one of claims 1 to 4.
8. The composite electrode material according to claim 7, characterized in that: The composite electrode material also includes an electrode active material; The multifunctional binder can form strong hydrogen bonds and ionic bonds with the electrode active material, thereby improving the cycle performance of the battery.
9. A battery pole piece, characterized in that: It comprises a current collector and a composite electrode material layer arranged on at least one side surface of the current collector, wherein the material of the composite electrode material layer comprises the composite electrode material as claimed in claim 7 or 8.
10. An electrochemical energy storage device, characterized in that: It comprises at least one of the multifunctional binder according to any one of claims 1 to 4, the composite electrode material according to claim 7 or 8, or the battery pole sheet according to claim 9; The electrochemical energy storage device is any one of a lithium ion battery, a sodium ion battery, a supercapacitor, a fuel cell or a solar cell.
Citation Information
Patent Citations
Composite binder for negative electrode of silicon-based lithium ion battery, preparation method of composite binder and silicon-based lithium ion battery
CN111384397A
Dendritic aqueous binder, negative electrode pole piece and battery, and preparation methods thereof
CN112159638A
Anode water-based binder for lithium battery and preparation method, electrode sheet preparing method
CN108832125A
Water-soluble binder, battery pole piece and application of water-soluble binder
CN117720869A
Anode fluoride-free binder material as well as preparation method and application thereof
CN117777904A
Cited By
Lithium-rich manganese-based positive pole piece for solid-state battery as well as preparation method and application of lithium-rich manganese-based positive pole piece
CN121394307A